2011
DOI: 10.1136/gutjnl-2011-301122
|View full text |Cite
|
Sign up to set email alerts
|

miR-150 as a potential biomarker associated with prognosis and therapeutic outcome in colorectal cancer

Abstract: The miR-150 expression status of patients with CRC is associated with survival and response to adjuvant chemotherapy. It is suggested that miR-150 should be considered as a potential biomarker associated with the prognosis and therapeutic outcome in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 20 publications
(16 reference statements)
7
119
0
2
Order By: Relevance
“…In solid tumor tissue, miR-150 expression levels were reduced when compared to paired non-cancerous tissue in colorectal cancer, indicating that low miR-150 expression is associated with shorter survival and a worse response to adjuvant chemotherapy (19). Our results demonstrated that miR-150 expression is also reduced in another solid tumor -NSCLC.…”
Section: A B C Dsupporting
confidence: 58%
“…In solid tumor tissue, miR-150 expression levels were reduced when compared to paired non-cancerous tissue in colorectal cancer, indicating that low miR-150 expression is associated with shorter survival and a worse response to adjuvant chemotherapy (19). Our results demonstrated that miR-150 expression is also reduced in another solid tumor -NSCLC.…”
Section: A B C Dsupporting
confidence: 58%
“…MicroRNA-150 deregulation has been reported in various cancers, including cutaneous T-cell lymphoma (28) and Burkitt lymphoma (29), as well as in solid cancers, such as in esophagi squamous carcinoma (30), non-small-cell lung carcinoma (31) and colorectal cancer (32). Surprisingly, cellular miR-150 upregulation was not always observed in tumoral tissue when compared with normal tissue; indeed, a lower level of cellular miR-150 is observed in esophagi (30), lung (31) and colorectal cancer (32) and T-cell lymphoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential prognostic value of miRNAs in CRC (15)(16)(17), the miRNA profiles were analyzed to examine their Adenomas in both distal colon and rectum and proximal colon. c Highest degree of histology.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in miRNA expression play a crucial role in human cancer (14). miRNAs have been shown to be a practical predictor associated with prognosis in CRC (15)(16)(17), and to be superior to mRNA, due to its small size, stability, and resistance to RNase degradation (18). Considering the potential prognostic value in CRC, we explored differentially expressed miRNAs from ACRAs with adenoma recurrence (RACRA) compared with ACRAs with no adenoma recurrence (NRACRA) to establish a predictor for adenoma recurrence.…”
Section: Introductionmentioning
confidence: 99%